Implementation of edupreneurship in preparing graduate competency achievements in elementary schools: A case study at SDN Cepokokuning Batang - Erma Yulaikah; Iin Purnamasari; Arri Handayani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to test and analyze: (1) Implementation of edupreneurship at SDN Cepokokuning Batang, (2) Achievement of graduate competencies, (3) Implementation of edupreneurship in preparing graduate competency achievements at SDN Cepokokuning. The research used a qualitative approach and a case study approach. The research subjects were grade VI students of SDN Cepokokuning, with 46 children. Data collection techniques from several research subjects were used, such as interviews, observations, and documentation studies. Qualitative data analysis was conducted interactively with the stages of (a) Data Reduction, (b) Data Display, and (c) Conclusion Drawing/ Verification. Based on the research results, the following conclusions can be drawn: (1) The implementation of edupreneurship at SDN Cepokokuning Batang involves the integration of entrepreneurial concepts in the learning process to equip students with practical skills and innovative mindsets through several implementation methods (a) project-based learning, (b) teaching factory, (c) collaboration with the business world, (d) development of business centers, (d) character education; (2) Graduate Competency Achievements (CKL) at SDN Cepokokuning Batang aim to provide a strong foundation in terms of attitude, knowledge, skills and character. Several general competency achievements for graduates of SDN Cepokokuning Batang: (a) attitude and character, (b) basic knowledge, (c) life skills, (d) independence; (3) The implementation of edupreneurship at SDN Cepokokuning Batang can help prepare graduate competency achievements by teaching creative, innovative, and entrepreneurial thinking skills from an early age. Several implementation methods can support the achievement of elementary school graduate competencies: (a) creative business-based projects, (b) learning from the surrounding environment, (c) collaboration in teams, (d) integration of subjects, (e) development of character and profile of Pancasila students.